(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The correlation between dielectric constant and pH of different soil types of southern part of Katsina state, Nigeria, was determined. The capacitance of the soil was measured using LCR Meter in order to calculate the dielectric constant of the soil. The calculated mean values of dielectric constant were found to be in the range of 3.90-25.60 with mean values of 7.95±1.64, 5.75±1.45, 5.01±0.37, 5.39±0.17, 5.43±0.49, 5.99±0.49, 6.29±0.49 and 5.38±0.21 for soil type Acrisols, Arenosols, Cambisols, Fluvisols, Leptosols, Lixisols, Luvisols and Regosols respectively. The mean pH values measured for each soil type ranges from 5.50-7.22 with a mean value of 6.38±0.05, 6.51±0.11, 6.26±0.13, 5.73±0.08, 6.15±0.16, 6.33±0.17, 6.44±0.12, and 6.56±0.07 for soil type Acrisols, Arenosols, Cambisols, Fluvisols, Leptosols, Lixisols, Luvisols and Regosols respectively. The correlation coefficient between dielectric constant and pH for soil types from the study area was found to indicate a weak correlation between the two soil parameters with a value of R = +0.30